1 | initial version |

In your case it would be something like this:

```
var('t');
x=function('x')(t)
y=function('y')(t)
de1 = diff(x,t) - diff(y,t) == x
de2 = diff(y,t) == y
desolve_system([de1, de2], [x,y])
```

and the result is as follow:

```
[x(t) == t*e^t*y(0) + e^t*x(0), y(t) == e^t*y(0)]
```

2 | No.2 Revision |

In your case it would be something like this:

```
var('t');
x=function('x')(t)
y=function('y')(t)
de1 = diff(x,t) - diff(y,t) == x
de2 = diff(y,t) == y
desolve_system([de1, de2], [x,y])
```

and the result is as ~~follow:~~follows:

```
[x(t) == t*e^t*y(0) + e^t*x(0), y(t) == e^t*y(0)]
```

Copyright Sage, 2010. Some rights reserved under creative commons license. Content on this site is licensed under a Creative Commons Attribution Share Alike 3.0 license.